Lower motor neuron facial palsy in a postnatal mother with COVID-19. Issue 3 (1st March 2021) - Kumar, Vignesh; Narayanan, Priyanka; Shetty, Seema; Mohammed, Afsal P
Abstract : COVID-19 is caused by the novel SARS-CoV-2 and is a potentially fatal disease that is of great global public health concern. In addition to respiratory symptoms, neurological manifestations have been associated with COVID-19. This is attributed to the neurotropic nature of coronaviruses. The authors present a case of Bell's palsy associated with COVID-19 in a term primigravida.